1986
DOI: 10.1111/j.1600-0714.1986.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced penetration of nitrosonornicotine across oral mucosa in the presence of ethanol

Abstract: There is evidence for synergy between tobacco and alcohol in the etiology of oral cancer but the reason for such an effect is unclear. One possible explanation is that alcohol enhances the penetration of carcinogens through the oral lining. We measured the permeability in vitro of three regions of porcine oral mucosa to the tobacco associated carcinogen, nitrosonornicotine (NNN) alone and in the presence of 5% or 50% ethanol. 50% ethanol did not significantly alter the permeability of oral mucosa to NNN except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 16 publications
3
50
1
2
Order By: Relevance
“…Evidence supports the hypothesis that the local permeabilizing effects of alcohol that facilitates the penetration of tobacco-specific carcinogens across oral mucosa may explain the synergy between tobacco and alcohol. Squier et al (54) showed that the penetration of nitrosonornicotine across the oral mucosa in the presence of nicotine is enhanced by alcohol. Du et al (55) and Howie et al (56) have shown that approximately 15% to 25% ethanol alone increased the permeability of the oral mucosa to tobacco carcinogens, such as N-nitrosonornicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports the hypothesis that the local permeabilizing effects of alcohol that facilitates the penetration of tobacco-specific carcinogens across oral mucosa may explain the synergy between tobacco and alcohol. Squier et al (54) showed that the penetration of nitrosonornicotine across the oral mucosa in the presence of nicotine is enhanced by alcohol. Du et al (55) and Howie et al (56) have shown that approximately 15% to 25% ethanol alone increased the permeability of the oral mucosa to tobacco carcinogens, such as N-nitrosonornicotine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have demonstrated that tobacco and alcohol products interact synergistically and increase each other's harmful effects. 2,3 The dehydrating effect of alcohol on cell walls enhances the ability of tobacco carcinogens to penetrate tissues. It is important to note, however, that a key difficulty in the study of tobacco and alcohol as risk factors is that most head and neck cancer patients have used both products.…”
Section: Summary Review/orthodontics Oral Cancermentioning
confidence: 99%
“…16 Alcohol on its own does cause damage to the oral mucosa and includes epithelial atrophy and decease in basal cell size atrophy with associated hyper-regeneration. 17 Against this background there is overwhelming evidence that mouthwashes are of value in reducing bacterial plaque and gingivitis and are useful adjuncts to mechanical methods of plaque removal.…”
Section: Safety and Efficacy Of Alco-hol Containing Mouthwashesmentioning
confidence: 99%